Узбекистан вступит в ЕАЭС: альтернативы нет - article Editorial (Евразийская интеграция: экономика, право, политика, 2020)
Источник: https://eadaily.com/ru/news/2020/09/03/uzbekistan-vstupit-v-eaes-alternativy-net?utm_campaign=main&utm_referrer=https%3A%2F%2Fpulse.mail.ru&utm_source=pulse_mail_ru